(untitled) (Nigerian Journal of Technology, 2003)
The paper presents a three step model of the dispersed flow heat transfer process, using an analysis of a single drop motion and heat transfer, and a statistical representation of the overall behaviour of the drops. The resulting equation gives the total heat transferred to the flow in terms of the mass flux, flow quality, fluid properties, wall roughness, and wall superheat. It includes the effect of contact angle or change in the wet ability of the surface. The range of validity of the model and the equation extends from dry wall film boiling to transition boiling, and is limited on the low temperature end by the critical Heat Flux region. Since the equation is analytically derived, its differentiation with respect to wall superheat will yield the Minimum Heat Flux point. The equation and model provide a very powerful base for analysis and prediction of post Critical Heat Flux heat transfer. The stable film boiling data for dispersed vertical flow of liquid nitrogen from reference [1] have been compared with the prediction and the results have been favourable.